1996
DOI: 10.1017/s0022336000038713
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of vertebrate trackways from the Permian of Scotland and related forms from Arizona and Germany

Abstract: The large number of ichnospecies in Permian vertebrate ichnology literature is often a result of a failure to recognize substrate or gait-controlled variations in trackway morphology. Additionally, regional studies were often performed in isolation from studies in other areas. Nomenclatural priority applies to the names first assigned to trackways from the Corncockle and Locharbriggs Sandstone Formations (Permian) of Dumfries and Galloway, Scotland. Only one ichnogenus, Chelichnus, and four ichnospecies are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

2000
2000
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 7 publications
1
46
0
1
Order By: Relevance
“…Identification of true tracks is further complicated in the fossil record where footprints undergo different stages of taphonomy and are at different stages within the diagenetic sequence of development. This corroborates Allen (1997) who stated that only a very small proportion of the tracks in a given area are capable of yielding diagnostic taxonomic information about the animals that made them, and McKeever and Haubold (1996) who showed that many Permian ichnogenera are nothing more than substrate or behavioral variants of the same trackmaker.…”
Section: Discussionsupporting
confidence: 84%
“…Identification of true tracks is further complicated in the fossil record where footprints undergo different stages of taphonomy and are at different stages within the diagenetic sequence of development. This corroborates Allen (1997) who stated that only a very small proportion of the tracks in a given area are capable of yielding diagnostic taxonomic information about the animals that made them, and McKeever and Haubold (1996) who showed that many Permian ichnogenera are nothing more than substrate or behavioral variants of the same trackmaker.…”
Section: Discussionsupporting
confidence: 84%
“…It is particularly important, therefore, to identify if and how foot anatomy has been obscured by sediment conditions and to exclude those preservational variants from ichnotaxonomic nomenclature. Indeed, the relatively large number of Late Permian vertebrate ichnospecies from the Corncockle and Locharbriggs Sandstone Formations of Dumfries and Galloway, Scotland, reflects the failure to recognize substrate variations in the development of track morphology (McKeever and Haubold, 1996). Many tracks of Chelichnus lyelli are of comparable size range to C. bucklandi, which those authors considered to be substrate-controlled variants of the latter.…”
Section: Implications For Paleobiology and Ichnotaxonomymentioning
confidence: 99%
“…Carboniferous, Permian and Jurassic tracks and trackways are well known from the rocks of Scotland (Clark 2001, Clark and Jewkes 2000, Clark and Barco Rodriguez 1998, Hopkins 1999, McKeever 1994, McKeever and Haubold 1996. Tracks from the Triassic are, however, poorly represented in Scotland despite a number of tetrapod remains being found from the Lower Norian Lossiemouth Sandstone Formation (Benton and Walker 1985).…”
Section: Introductionmentioning
confidence: 99%